Polarization-dependent extraordinary optical transmission from upconversion nanoparticles. Issue 43 (21st October 2015) - Wang, Peng Hui; Salcedo, Walter J.; Pichaandi, Jothirmayanantham; van Veggel, Frank C. J. M.; Brolo, Alexandre G.
Abstract : Enhanced upconversion (UC) emission was experimentally demonstrated using gold double antenna nanoparticles coupled to nanoslits in gold films. Abstract : Enhanced upconversion (UC) emission was experimentally demonstrated using gold double antenna nanoparticles coupled to nanoslits in gold films. The transmitted red emission from UC ytterbium and erbium co-doped sodium yttrium fluoride (NaYF4 :Yb 3+ /Er 3+ ) nanoparticles (UC NPs) at ∼665 nm (excited with a 980 nm diode laser) was enhanced relative to the green emission at ∼550 nm. The relatively enhanced UC NP emission could be tuned by the different polarization-dependent extraordinary optical transmission modes coupled to the gold nanostructures. Finite-difference time-domain calculations suggest that the preferential enhanced UC emission is related to a combination of different surface plasmon mode excitation coupling to cavity Fabry-Perot interactions. A maximum UC enhancement of 6-fold was measured for nanoslit arrays in the absence of the double antennas. In the presence of the double nanoantennas inside the nanoslits, the UC enhancement was between 2- and 4-fold, depending on the experimental conditions.